The The Relative Tensile Outcome of E60 and E70 Electrodes Deposits on Low Carbon Steel Welded Joints: Tensile Test - Alhassan, Munkaila (European Journal of Applied Sciences, 2021)
Abstract: The responsive nature of low carbon steel to various applications such as fabrication works, construction and maintenance cannot be overemphasized. In most applications of low carbon steel there is the necessity to provide welding joints. In the majority of cases, the E6013 and E7018 electrodes are generally used. This study was designed to examine the influence of these electrodes on the tensile characteristics of welded low carbon steel of grade, AISI 1018. The test was conducted after preparing the joints and welding with shielded metal arc welding (SMAW) process. The results showed that the yield point for E6013 was 392.8N/mm2 and that of E7018 deposits was 443N/mm2, suggesting that E7018 deposit is relatively higher in yield point than the E6013. The results also revealed that the E7018 electrode has higher tensile deposit in relation to E6013 electrode. Clearly, the E6013 deposit has lower UTS as compared with E7018. Basically the E6013 deposit will fracture before the E7018 deposit when a tensile force is applied. It is therefore recommended that the E7018 electrode be used for when higher tensile deposit on low carbon steel required. If however a lower tensile deposit is required on low carbon steel the E6013 electrode could be used.